Tourism, culture and creativity: The case of the CREATOUR project in the Alentejo/Portugal region - MARUJO, NOÉMI (2021)
Relations between tourism and the creative industries differ from those between tourism and culture, but may have significant affinities in some territories. However, there are few empirical studies in the scientific literature that address the possible connections between them in Portugal, despite their unquestionable interest. For this reason, this article presents how the CREATOUR project put tourism, culture and creativity in dialogue in the tourist destination of Alentejo, in Portugal. We used the case study as a research strategy, followed by content analysis of several informative records which were generated meanwhile by the multiple work dynamics of the project itself. The results show that creative tourism has a significant relationship with cultural tourism and is an important instrument to enhance the development of rural territories in the region studied, provided that several premises are considered